Lipoma arborescens of the elbow - K Ranganath (Indian Journal of Radiology and Imaging, 2010)
Lipoma arborescens (LA) is a rare non-neoplastic intra-articular lesion that most commonly affects the knee joint, especially the suprapatellar bursa. It rarely affects the elbow joint. There are a few reports of involvement of the bicipital radial bursa. We report a case of LA, with characteristic MRI features, affecting the elbow joint in a young male.